Attitudes of ULIS first-year international business English students towards the application of case studies in English 2a – business - Nguyễn, Ngọc Thu Trang (ĐHQGHN - Trường Đại học Ngoại Ngữ, 2021)
With a scrutiny into the process of conducting case studies by first-year students in the International Business English program, FELTE, ULIS, the research aims at: (1) reporting students' perceptions of the effectiveness of case studies in enhancing pivotal skills for business careers, (2) determining the demotivating factors that students may encounter when doing case studies and (3) offering recommendations to overcome demotivation and make the best use of case studies in Business English lessons. To achieve the above objectives, the research uses a combination of quantitative and qualitative methods with questionnaire and semi-structured interview as main data collection instruments. The result reveals that as perceived by students, case studies enormously contribute to their development in various essential skills for their future careers such as business communication skills, problem-solving skill and decisionmaking skill. In addition, students face numerous sources of demotivation in doing case studies. Their demotivation originates from diverse factors: students themselves, learning materials, teachers and learning environment, which suggests reconsideration and comprehensive changes for improvement.